Capacitive Feedthroughs for Medical Implants - Grob, Sven; Tass, Peter A.; Hauptmann, Christian (Frontiers in Neuroscience, 2016)
Important technological advances in the last decades paved the way for a great success story for electrically stimulating medical implants, including cochlear implants or implants for deep brain stimulation. However, there are still many challenges in reducing side effects and improving functionality and comfort for the patient. Two of the main challenges are the wish for smaller implants on one hand, and the demand for more stimulation channels on the other hand. But these two aims lead to a conflict of interests. This paper presents a novel design for an electrical feedthrough, the so called capacitive feedthrough, which allows both reducing the size and increasing the number of included channels. Capacitive feedthroughs include the functionality of a coupling capacitor and an electrical feedthrough within one and the same structure. The paper also discusses the progress and the challenges of the first produced test structures. The concept bears a high potential in improving current feedthrough technology, and could be applied for all kinds of electrical medical implants.